2022
DOI: 10.1002/adfm.202204273
|View full text |Cite
|
Sign up to set email alerts
|

Inosine‐Based Supramolecular Hydrogel for Highly Efficient PD‐L1 Blockade Therapy via Mediating CD8+ T Cells

Abstract: Inosine is proven to promote the proliferation and function of CD8+ cytotoxic lymphocytes (CD8+ T) under glucose restriction and enhance the efficacy of programmed cell death protein ligand‐1 (PD‐L1) blockade therapy. However, systemic administration of high frequencies and large doses of inosine and anti‐PD‐L1 antibody (aPDL1) is required, which inevitably reduces bioavailability and causes severe immunological side effects. Therefore, it is crucial to develop a drug delivery system to achieve gradient releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…This is attributed to the regulation of glycolytic metabolism in tumor cells, which reversed the tumor immunosuppressive microenvironment and undoubtedly gave CAR T cells a more favorable living space. Notably, immunomodulatory CD4 + T cells and cytotoxic CD8 + T cells are two characteristic manifestations of CAR T cell activation and differentiation and also the main effectors that trigger the body’s antitumor immune response . As shown in Figure b,c, synergistic therapy (APHA@CM+US+NIR), as a way to drive ICD in tumor cells, promoted the differentiation of CD4 + /CD8 + CAR T cells more pronouncedly than APHA@CM alone, causing stronger T cell activation.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…This is attributed to the regulation of glycolytic metabolism in tumor cells, which reversed the tumor immunosuppressive microenvironment and undoubtedly gave CAR T cells a more favorable living space. Notably, immunomodulatory CD4 + T cells and cytotoxic CD8 + T cells are two characteristic manifestations of CAR T cell activation and differentiation and also the main effectors that trigger the body’s antitumor immune response . As shown in Figure b,c, synergistic therapy (APHA@CM+US+NIR), as a way to drive ICD in tumor cells, promoted the differentiation of CD4 + /CD8 + CAR T cells more pronouncedly than APHA@CM alone, causing stronger T cell activation.…”
Section: Resultsmentioning
confidence: 79%
“…Notably, immunomodulatory CD4 + T cells and cytotoxic CD8 + T cells are two characteristic manifestations of CAR T cell activation and differentiation and also the main effectors that trigger the body's antitumor immune response. 46 As shown in Figure 6b,c, synergistic therapy (APHA@CM+US+NIR), as a way to drive ICD in tumor cells, promoted the differentiation of CD4 + /CD8 + CAR T cells more pronouncedly than APHA@CM alone, causing stronger T cell activation. Notably, the activated CAR T cells induced large-scale outbreaks of granzyme B, perforin, and IFN-γ (Figure 6d−f), which were an effective weapon to kill tumor cells and accelerate the death process of tumor cells.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Considering these issues, we aimed to seek an inexpensive and efficient matter that targets certain oncoproteins and could be integrated into our dual-functional hydrogel. In this study, to establish a stable system, we selected potassium as the core of PCA due to its proper diameter, which was suitable to act as the core of the isoG quartet, and we observed that PCA and isoG could form a stable and injectable hydrogel following several simple steps. This modality was endowed with targeted bioactivity due to the involvement of PCA.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above presumption, we initially investigated the expression and biological function of Sb9 in OSCC. After confirming that cancer cell death could be triggered by inhibiting Sb9 expression, we designed and constructed the isoguanosine (isoG)-phenylenebisboronic acid (PBA)-PCA supramolecular hydrogel (PCA gel) by introducing a dynamic covalent borate ester bond using simple procedures in the presence of potassium, which was the most suitable core of the isoG-related hydrogel due to its proper diameter according to previous works. This is the first time a local delivery system has been reported for PCA. Various experimental techniques were used to confirm the structure and properties of the PCA gel.…”
Section: Introductionmentioning
confidence: 99%